The Cooperation Council for the Arab States of the Gulf: History, Key Achievements and Development Prospects - E. S. Melkumyan (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Cooperation Council for the Arab States of the Gulf (the Gulf Cooperation Council, GCC) is one of the key regional organizations and its significance has only augmented in recent years. Meanwhile, the author emphasizes that both Russian and foreign academic literature on the topic lacks general works covering activities of the organization. This paper aims to partially fill this gap. It highlights specific features of political systems of the GCC states, the institutional structure and the main directions of this organization’s activity: from economics and finances to security and common defense policy. The author emphasizes that the GCC’s ability to adopt a joint position based on a compromise should be credited to the leaders of the member-states. However, the paper outlines a range of issues impeding effective realization of the goals proclaimed by the organization. Particularly, the author focuses on the differences of opinion among the GCC countries on military cooperation and transformation of the organization into a full-fledged alliance. The Arab Awakening became another major challenge for all states of the Gulf. The paper examines how the ruling regimes of the GCC states were forced to respond to the unfurling of the wave of popular protests in their countries. Nevertheless, the author stresses that the GCC states managed to prove solidity of their political regimes, and the organization as a whole increased its impact in the region. Finally, the paper dwells on the events of the so called Qatar crisis, resulting from the discontent among the majority of GCC states with Qatar, which they accuse of supporting terrorist organizations. The author concludes that the Qatar crisis has demonstrated that national interests and the desire to maintain national sovereignty tend to have preference in the policy of the Gulf States over the common goals of the GCC. However, the GCC leaders strive to revive the spirit of cooperation and since the GCC members are interested in strengthening their cooperation, the organization could meet the challenges it has faced.